2009
DOI: 10.1038/emboj.2009.365
|View full text |Cite
|
Sign up to set email alerts
|

Functional involvement of Tudor and dPRMT5 in the piRNA processing pathway in Drosophila germlines

Abstract: In Drosophila, the PIWI proteins, Aubergine (Aub), AGO3, and Piwi are expressed in germlines and function in silencing transposons by associating with PIWI-interacting RNAs (piRNAs). Recent studies show that PIWI proteins contain symmetric dimethyl-arginines (sDMAs) and that dPRMT5/Capsuleen/DART5 is the modifying enzyme. Here, we show that Tudor (Tud), one of Tud domaincontaining proteins, associates with Aub and AGO3, specifically through their sDMA modifications and that these three proteins form heteromeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
237
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(254 citation statements)
references
References 44 publications
11
237
0
2
Order By: Relevance
“…BmSpn-E depletion resulted in decreased levels of both SIWI-and BmAGO3-bound piRNAs, whereas BmTUDOR depletion increased the levels of the piRNAs. These results are in agreement with previous reports on Drosophila ovaries which implicated Spn-E and TUDOR in piRNA biogenesis, and showed that piRNA levels were severely decreased in spn-E mutant flies and that tudor mutant contained increased piRNA levels (Lim and Kai 2007;Nishida et al 2009). Strikingly, as observed in sDMA-lacking BmAGO3-bound piRNAs, the BmPAPI depletion did not affect quantity but increased the lengths of both SIWI-and BmAGO3-bound piRNAs (Fig.…”
Section: M1 M3supporting
confidence: 83%
See 2 more Smart Citations
“…BmSpn-E depletion resulted in decreased levels of both SIWI-and BmAGO3-bound piRNAs, whereas BmTUDOR depletion increased the levels of the piRNAs. These results are in agreement with previous reports on Drosophila ovaries which implicated Spn-E and TUDOR in piRNA biogenesis, and showed that piRNA levels were severely decreased in spn-E mutant flies and that tudor mutant contained increased piRNA levels (Lim and Kai 2007;Nishida et al 2009). Strikingly, as observed in sDMA-lacking BmAGO3-bound piRNAs, the BmPAPI depletion did not affect quantity but increased the lengths of both SIWI-and BmAGO3-bound piRNAs (Fig.…”
Section: M1 M3supporting
confidence: 83%
“…The availability of efficient and convenient plasmid transfection and RNAi gene silencing techniques make BmN4 an ideal system to explore the function of TUDOR proteins, and we identified BmPAPI, BmSpn-E, and BmTUDOR as the Bombyx TUDOR proteins responsible for piRNA biogenesis. We were able to recapitulate in BmN4 cells the piRNA behaviors described previously in spn-E and tudor mutant flies (Lim and Kai 2007;Nishida et al 2009): BmSpn-E or BmTUDOR depletion by RNAi resulted in severe decreases or increases in piRNA levels, respectively.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the testes, these two proteins associate with other piRNA pathway components including Vasa (Vas), Armitage (Armi), and Tudor (Tud) in large electron-dense perinuclear bodies, dubbed piNG-bodies, which are thought to regulate the processing and/or targeting of piRNAs to transposable elements via sequence homology (Lim and Kai 2007;Lim et al 2009;Nishida et al 2009;Kibanov et al 2011). The localization of both Aub and AGO3 to this perinuclear region is codependent; loss of one protein through mutation results in mislocalization of the other (Cox et al 2000;Brennecke et al 2007;Nishida et al 2007;Li et al 2009;Nagao et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…26 The arginine-glycine rich domain (a.k.a. RG domain, aminoacids [11][12][13][14][15][16][17] is necessary to interact with Tudor proteins; 27,28 the PAZ domain (Piwi-ArgonautZwille) located on the N terminal half (aminoacids 280-413) serves as a docking site for 3 0 end of small RNA; 29 and the PIWI domain, located on the C-terminal half (amino acids 554-852) of the protein having a function similar to RNase H 30 ( Fig. 1A).…”
Section: Molecular Characterization Of the Aub Qc42 Allelementioning
confidence: 99%